PENGARUH PENJUALAN BERSIH, BIAYA OPERASIONAL DAN STRUKTUR MODAL TERHADAP PAJAK PENGHASILAN BADAN TERUTANG PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Junaidi Siahaan; Dame Ria Rananta Saragi; Lasma Lenida Rosinta Sianipar (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This research aims to prove that net sales, operational costs and capital structure (Long-term Debt to Asset Ratio) have an influence on the Corporate Income Tax payable in Consumer Goods Industry Sector Companies listed on the Indonesia Stock Exchange in 2021-2023. The sample in this study was obtained by purposive sampling, with a total sample of 29 companies. The data analysis technique used is multiple linear regression and hypothesis testing using the t test and f test with a significance level of 5% using SPSS 21. The results of research using SPSS, it is known that the coefficient of determination (R Square) is 0.691. Net sales, operational costs and capital structure (Longterm Debt to Asset Ratio) together influence the Corporate Income Tax payable, namely 69.1%. Based on the results of multiple linear regression analysis, it can be concluded that net sales have a significant positive effect on Corporate Income Tax payable, operational costs have an insignificant positive effect on Corporate Income Tax payable and capital structure (Longterm Debt to Asset Ratio) has a significant negative effect on Corporate Income Tax payable to the company consumer goods industry sector listed on the Indonesia Stock Exchange in 2021-2023. The higher the net sales, operational costs and capital structure (Longterm Debt to Asset Ratio), the more it will affect the Corporate Income Tax payable.